2016
DOI: 10.3390/ijerph13050494
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Asbestos-Related Disease in Countries Currently Using Asbestos

Abstract: More than 40 years of evaluation have consistently confirmed the carcinogenicity of asbestos in all of its forms. This notwithstanding, according to recent figures, the annual world production of asbestos is approximatively 2,000,000 tons. Currently, about 90% of world asbestos comes from four countries: Russia, China, Brazil and Kazakhstan; and the wide use of asbestos worldwide represents a global threat. The purpose of this paper is to present a review of the asbestos health impact and to discuss the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 64 publications
(72 reference statements)
0
44
0
2
Order By: Relevance
“…6 In 2016, about 80% of the global population was living in countries without a total asbestos ban. 11 Because of scant regulation or poor regulatory oversight, people are frequently exposed to hazardous substances at work. The Global Burden of Diseases, Injuries and Risk Factors Study (GBD) estimated that, in 2017, 29 909 people worldwide died from mesothelioma, including 27 447 from occupational causes and 2462 from nonoccupational causes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…6 In 2016, about 80% of the global population was living in countries without a total asbestos ban. 11 Because of scant regulation or poor regulatory oversight, people are frequently exposed to hazardous substances at work. The Global Burden of Diseases, Injuries and Risk Factors Study (GBD) estimated that, in 2017, 29 909 people worldwide died from mesothelioma, including 27 447 from occupational causes and 2462 from nonoccupational causes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The first epidemiological studies of cancer risk in relation to exposure to asbestos were reported in the 1950s (Marsili et al 2016). Until the late 1970s, asbestos was used in construction products such as asbestos insulation, roofing, flooring, adhesives, duct connectors as well as protective clothing, household items, and others.…”
Section: Association Between Potential Health Outcomes and Chemical Hmentioning
confidence: 99%
“…The first suspected asbestos-related lung cancers were reported by Gloyne in 1935 upon autopsies of two female asbestos textile factory workers who were found to suffer from asbestosis and lung cancer [8]. More cases of asbestos-related cancers have been diagnosed since that time and since 1987 asbestos has been classified by the International Agency for Research on Cancer of the World Health Organization as being carcinogenic to humans [9,10].…”
Section: Introductionmentioning
confidence: 99%